Numerical and experimental research of helical gear contact stress considering the influence of friction - Yang, Xiaopeng; Yin, Shunliang; Chen, Yong; Zhang, Yong; Zhang, Shuang; Wu, Yimin (Frontiers in Mechanical Engineering, 2022)
Helical gears are widely used in various mechanical transmissions. Thus, analysing gear contact stresses is crucial to improve the fatigue limit and life of gears. The effect of coefficient of friction on the contact stress of helical gears is analysed in this paper, with given coefficients of friction. The following results are obtained. (1) The contact stress increases with the coefficient of friction in the early stage of meshing. (2) The contact stress decreases with the in-crease in the coefficient of friction in the late stage of meshing. (3) The gear contact fatigue test shows that the loca-tion of fatigue pitting on the tooth surface is consistent with that of the simulated maximum stress point. The friction-reducing coating on the gear surface can decrease the coefficient of friction between the tooth surfaces and thus ef-fectively improve the gear contact fatigue life.